PERSEPSI MAHASISWA AKUNTANSI TERHADAP PENYUSUNAN LAPORAN KEUANGAN - Kurniasari, Dian (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2017)
One of the goals of accounting education in Indonesia is to introducethe students to the ethics and values of accounting profession. This researchfocused on the effectiveness of acconting curiculum in developing studentsresponsibility towards the financial statement’s users. We find that differentethics influence to perception the financial statement.